The Effect of Short Videos on Vocabulary Mastery among Students of Al-Amin Tingaf Islamic Elementary School East Jakarta - Mia Muth Mainnah; Iman Matin; Achmad Fudhaili (INTIFA: Journal of Education and Language, 2026)
This study aims to analyze the effectiveness of short videos in enhancing vocabulary mastery and to explore students’ perceptions of using short video content in Arabic language learning at Al-Amin Tingaf Islamic Elementary School. The research used a quantitative quasi-experimental design with 48 students divided into two groups: 24 in the experimental group and 24 in the control group. The experimental group received vocabulary instruction through short videos, while the control group learned through traditional methods. Data were collected through pretests, posttests, and a student perception questionnaire. The results showed that the experimental group’s average score increased from 66 on the pretest to 83.6 on the posttest, with an improvement of 16.5 points. However, the T-test indicated that the difference was not statistically significant (Sig. > 0.05). Despite this, the questionnaire revealed positive student responses, especially regarding the attractiveness and clarity of the short video content. Overall, short videos demonstrate promising potential as an engaging and supportive tool for teaching Arabic vocabulary.